2015
DOI: 10.1111/crj.12379
|View full text |Cite
|
Sign up to set email alerts
|

Overview of antimicrobial options for Mycoplasma pneumoniae pneumonia: focus on macrolide resistance

Abstract: The problem of macrolide resistant M. pneumonia is emerging. Antibiotic stewardship is needed to inhibit the inappropriate use of macrolide and new antibiotics with a more acceptable safety profile for all ages need to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 90 publications
(142 reference statements)
2
35
0
Order By: Relevance
“…In the present study, we found that 80% of MP isolated strains were resistant to ERY, and 72% were resistant to AZM. Fifty-five ERYresistant MP strains harbored an A2063G transition in the 23S rRNA genes and one harbored an A2064G transition, which was consistent with previous reports that the A2063G transition was the most frequent mutation related to macrolides resistance (2,10). Further, it is interesting to note that 6 strains with mild to moderate ERY-resistance level were still susceptible to AZM, among which only 2 strains (MIC value 16 and 32 μg/mL, respectively) harbored an A2063G transition.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, we found that 80% of MP isolated strains were resistant to ERY, and 72% were resistant to AZM. Fifty-five ERYresistant MP strains harbored an A2063G transition in the 23S rRNA genes and one harbored an A2064G transition, which was consistent with previous reports that the A2063G transition was the most frequent mutation related to macrolides resistance (2,10). Further, it is interesting to note that 6 strains with mild to moderate ERY-resistance level were still susceptible to AZM, among which only 2 strains (MIC value 16 and 32 μg/mL, respectively) harbored an A2063G transition.…”
Section: Discussionsupporting
confidence: 89%
“…Mutations in the sequence of 23S rRNA, A2063G was the most prevalent, followed by A2064G, A2063T and A1290G. A2063G and A2064G mutations are always responsible for the high-level macrolide resistance in MP (2). In the present study, we found that 80% of MP isolated strains were resistant to ERY, and 72% were resistant to AZM.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations